Modeling grouped survival data with time-dependent covariates - Silveira Chalita, Liciana V. A.; Colosimo, Enrico A.; De Souza Passos, Jose Raimundo (Taylor & Francis Inc, 2006)
In this article, proportional hazards and logistic models for grouped survival data were extended to incorporate time-dependent covariates. The extension was motivated by a forestry experiment designed to compare five different water stresses in Eucalyptus grandis seedlings. The response was the seedling lifetime. The data set was grouped since there were just three occasions in which the seedlings was visited by the researcher. In each of these occasions also the shoot height was measured and therefore it is a time-dependent covariate. Both extended models were used in this example, and the results were very similar.
Keywords: discrete models; interval censoring; logistic model; proportional hazards model; water stress